Thematic Structure, Evolution, and Authorship Patterns of Physical Education Theory and Methodology (2019–2025) - Khudolii, Oleg; Ivashchenko, Olha (Physical Education Theory and Methodology, 2026)
Background. Bibliometric analyses provide an evidence-based approach for examining the thematic orientation, development trajectories, and collaboration patterns of scientific journals. Purpose. The purpose of this study was to analyze the thematic structure, thematic evolution, and authorship patterns of publications in Physical Education Theory and Methodology (PETM) during 2019–2025. Methods. Scopus-indexed metadata were analyzed using bibliometric methods. A weighted keyword co-occurrence network was constructed and examined using the Louvain community detection algorithm. Thematic evolution was assessed across three periods (2019–2020, 2021–2022, 2023–2025), and recurrent co-authorship patterns were identified based on indexed author records. Results. Five major thematic clusters representing the core research domains of PETM were identified. Thematic evolution analysis revealed a cumulative development pattern characterized by stable methodological foundations and pronounced growth in health-related, assessment-oriented, and integrative applied research. Authorship analysis demonstrated the presence of recurring author teams and stable collaborative structures. Conclusions. The findings provide quantitative evidence of PETM’s controlled thematic diversification and support its positioning as a methodologically grounded journal with expanding international relevance. The results may inform editorial positioning, scope refinement, and future policy development.